GLASS-IONOMER MODIFIKASI RESIN - Bambang Irawan Sosrosoedirdjo (Faculty of Dentistry, Universitas Indonesia, 2015)
Development of ideal dental materials to replace tooth tissue has been the objective of many researchers and manufacturers. Consequently, a wide range of dental materials with different chemical compositions, properties and recommendations on clinical application has been introduced in dentistry. Conventional glass-ionomers (GIC) were introduced to the dental profession by Wilson and Kent in 1972. The adhesion of these materials to dental tissue and their fluoride releasing capacity brought about their use as restoration bases and cement. In 1988, resin-modified glass-ionomer cements were developed to improve the high sensitivity to humidity and low mechanical strength of glass-ionomers. The new resin modified glass-ionomer cements have produced materials with superior properties. However, these improvements are as yet insufficient for these materials to compete with the resin composites in high stress bearing situations such as incisal tip restorations and posterior occlusal restorations in the permanent dentition.